Thermo-Hydro-Mechanical Coupled Modeling of Methane Hydrate-Bearing Sediments: Formulation and Application - Maria De La Fuente; Jean Vaunat; Héctor Marín-Moreno (Energies, 2019)
We present a fully coupled thermo-hydro-mechanical formulation for the simulation of sediment deformation, fluid and heat transport and fluid/solid phase transformations occurring in methane hydrate geological systems. We reformulate the governing equations of energy and mass balance of the Code_Bright simulator to incorporate hydrate as a new pore phase. The formulation also integrates the constitutive model Hydrate-CASM to capture the effect of hydrate saturation in the mechanical response of the sediment. The thermo-hydraulic capabilities of the formulation are validated against the results from a series of state-of-the-art simulators involved in the first international gas hydrate code comparison study developed by the NETL-USGS. The coupling with the mechanical formulation is investigated by modeling synthetic dissociation tests and validated by reproducing published experimental data from triaxial tests performed in hydrate-bearing sands dissociated via depressurization. Our results show that the formulation captures the dominant mass and heat transfer phenomena occurring during hydrate dissociation and reproduces the stress release and volumetric deformation associated with this process. They also show that the hydrate production method has a strong influence on sediment deformation.